Quality Policy and Competitiveness of the Country - Slatkevičienė, Giedrė; Adomaitienė, Roma; Ruzevičius, Juozas (Ekonomika, 2005)
For survival and institutionalization in the European and world markets, Lithuania needs to create and develop competitive economy, assure the wealth of its society by seeking quality of organizations, their goods and services. The purpose of this study is to formulate possible references of national quality policy and the system of its implementation tools.In the article, attitudes of European Quality Promotion Policy are reviewed; European Quality Vision created by European Quality Organization is analysed; the real situation in the area of quality assurance in Lithuania is summarized. There are proposed and reasoned elements of Quality Policy of Lithuania and the means of its implementation that should meet the requirements, actions and official documents used in the European Union.A comparative systematic analysis of scientific literature, legal acts, sources of information, methaanalysis, survey for business representatives were used for the study.